Gustaw Herling-Grudziński Dnevnik pisan noću (ruski za logor, engleski za rat, italijanski za tuđinu, poljski za noć). Ne prevoditi da bi se razumjelo - Ljevo-Ovčina, Amela (Przekłady Literatur Słowiańskich, 2019)
Literature may stand in opposition to any theory, and so, even those theories which are marked by conspicuous theses, hardly provide readers with sufficient, compelling interpretations. Gustaw Herling-Grudziński in his Diary Written at Night assumes the reader’s vantage point. He writes of what he sees, reads, and what he can remember, but also of what is really important. In the Diary we may witness a Pole who, despite being an outstanding intermediary, does not take liberty to explain in order to elucidate new things, but merely reads and comprehends the world, approaching reality also by means of languages and cultures through which Goodness is expressed.